Research Conference on Structure and Properties of Engineering Materials, held March 12-13, 1962 at North Carolina State College, Raleigh, NC : proceedings - Research Conference on Structure and Properties of Engineering Materials (1962 : Raleigh, NC); Stadelmaier, H. H.; Austin, W. W. (New York : Plenum Pr., 1963)
PSZJBL